Evaluation of Diabetic Child’s Mother Stressors - جبيلي, ابتسام (Latakia University Journal -Medical Sciences Series, 2024)
Today, psychological stress is considered one of the most widespread psychological and social phenomena in societies. Therefore, the moment in which a child’s illness is discovered in the family is a decisive stage that leads to a radical change for the family in general and for the mother in particular. However, regardless of the information available about diabetes, she must experience some surprise, fear, disbelief, sadness, anger, and guilt, and this Which leads to being in psychologically stressful situations. Therefore, the study aimed to identify her level of psychological stress, using the psychological stress perception index regarding the quality of life and strategies for dealing with psychological stress for the mother of a child with diabetes. The study population included all mothers of children with type 1 diabetes using the descriptive approach. A non-random, purposive sample was selected from mothers who accompanied their children during visits to the Diabetes Center of the Health Directorate in Lattakia. Their number reached 25 during the data collection period. The results of our study showed that mothers of children have an average level of not feeling comfortable, unable to do the things they love, do not feel as calm as they should, are not full of vitality, do not feel protected and safe, do not enjoy themselves with what they want, and are not a free person. Of worries. Our study also showed that mothers have a high level of psychological stress due to fear for their children about the future. Our study did not show any statistically significant differences in the level of stress according to the variable of age and work, with there being differences attributed to the variable of educational level in favor of university women who had a lower level of psychological stress.